The platelet defect in acute myeloid leukaemia. Issue 12 (December 1984) - Woodcock, B E; Cooper, P C; Brown, P R; Pickering, C; Winfield, D A; Preston, F E
Abstract : In a study of platelets from 13 patients with acute myeloid leukaemia abnormal aggregation and release reactions were found. A previously unrecognised quantitative defect of thromboxane B2 production may, at least in part, explain these findings. In contrast to a previous report, we were unable to show a convincing storage pool defect in these platelets. The platelet membrane glycoproteins were largely normal.